ДНК микоплазм содержат фрагменты, гомологичные длинным концевым повторам вируса Раушера - Борхсениус, С.Н.; Раковская, И.В.; Чернова, О.А.; Меркулова, Н.А. (Биополимеры и клетка, 1988)
Обнаружено, что EcoRV-фрагменты ДНК микоплазм, содержащие гены рРНК, гомологичны длинным концевым повторам вируса Раушера (LTR RLV). Обнаруженная гомология LTR RLV и ДНК микоплазм является предпосылкой для обмена генетической информацией между вирусами и микоплазмой. Виявлено, що EcoRV-фрагменти ДНК мікоплазм, що містять гени рРНК, гомологічні довгим кінцевим повторам вірусу Раушера (LTR RLV). Виявлена гомологія LTR RLV і ДНК мікоплазм є передумовою для обміну генетичною інформацією між вірусами і мікоплазмою. Mycoplasmas activate persistent and oncogenous viruses. The mycoplasma-virus-mammalian cell system is of interest to clarify the possible interaction of these organisms on the genome level. It is found that DNA EcoRV-iragmenis containing rRNA genes of mycoplasmas (A. laidlawii, M. arthritidls, M. gallisepticum, M. mycoides subsp. capri) are homologous to long terminal repeats of Rauscher leukemia virus (LTR RLV). The same EcoRV-fragments of A. laidlawii are homologous to sites of eukaryotic topoisomerase I (Top I). It is conceivable that LTR RLV contain Top I sites and the observed effect is a consequence of these sites homology. The revealed homology of LTR RLV with DNAs of mycoplasmas is a promise for genome exchange between viruses and mycoplasmas.